THE INFLUENCE OF FINANCIAL PERFORMANCE ON ECONOMIC GROWTH IN SUBANG REGENCY - Marina Trozi Dahliyana (UPT Publikasi Ilmiah UNISBA, 2025)
This study analyzes the Regional Financial Efficiency Ratio and the Local Own-source Revenue Effectiveness Ratio from 2014 to 2023 to understand their impact on economic growth in Subang Regency. This research uses a quantitative approach with a type of descriptive research. Using secondary data from the Central Statistic Agency and Local Financial Government’s Report from The Audit Board of The Republic of Indonesia. This study applies multiple linear regression analysis processed using SPSS 25 software . The result of research shows that the significance value of Regional Financial Efficiency is 0.012, which is less than 0.05, with a regression coefficient of 3.939. This indicates that the Regional Financial Efficiency Ratio has a positive and significant effect on Economic Growth. The significance value of the Regional Own-Source Revenue Effectiveness is 0.010, which is also less than 0.05, with a regression coefficient of 6.631. This means that this ratio has a positive and significant effect on Economic Growth.